Quantum dot photoresist film and preparation method thereof
By adding selenium-tributylphosphine precursor to a high-concentration cadmium selenide nucleus to a high-temperature reaction, the problem of low light conversion efficiency in traditional quantum dot photoresist composite films is solved. The blue light conversion efficiency of Micro-LED chip is improved and the exposure effect of photoresist is maintained.
Patent Information
- Application Number
- CN202411286453.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-13
AI Technical Summary
The quantum dot light conversion efficiency in traditional quantum dot photoresist composite films is low, resulting in the escape of blue light from Micro-LED chips. Increasing the quantum dot concentration will affect the exposure effect of the photoresist.
The addition of selenium-tributylphosphine precursor under high temperature reactions is used to synthesize high-concentration cadmium selenide nuclei to prepare green luminescent CdSe/CdS quantum dots, which does not affect the absorbance at 365 nanometers by increasing the mass absorption coefficient at 450 nanometers. , enhance the light conversion efficiency.
The quantum dot light conversion efficiency in the quantum dot photoresist composite film is effectively improved, avoiding the escape of blue light from Micro-LED chips, and maintaining the exposure effect of the photoresist.
Smart Images

Figure CN119126489A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new material technology, and in particular to a quantum dot photoresist film and a preparation method thereof. Background Art
[0002] In terms of Micro-LED full-color display technology, the current optimal technical solution is based on blue-light-emitting Micro-LED chips, combined with the pixelation of red and green quantum dots, and finally achieves full-color display through wavelength conversion solutions. However, the blue light conversion efficiency of quantum dots obtained by the traditional method of achieving full-color display through the pixelation of quantum dot photoresist is low, and an additional layer of red or green filter is required to reduce the escape of blue light from the Micro-LED chip. Although the optical density of blue light of quantum dot photoresist film can be increased to a certain extent by increasing the concentration of quantum dots in photoresist, the dispersibility of quantum dots in photoresist is limited and cannot be increased indefinitely. According to practical experience, when the mass fraction reaches about 10%, the dispersibility of quantum dots in photoresist is difficult to maintain. At the same time, by increasing the concentration of quantum dots, not only the optical density at 450 nanometers (blue light) is increased, but also the absorbance at 365 nanometers (ultraviolet light) is greatly improved. As a result, most of the energy of the lithography light source will be absorbed by the quantum dot material in the quantum dot photoresist composite system, which ultimately seriously affects the exposure of the photoresist and makes it impossible to obtain an effective quantum dot photoresist composite film. Summary of the invention
[0003] The main technical problem solved by the implementation methods of the present application is that the quantum dot light conversion efficiency in the traditional quantum dot photoresist composite film is low, resulting in the escape of blue light from the Micro-LED chip.
[0004] In order to solve the above technical problems, a technical solution adopted in the embodiment of the present application is: to provide a method for preparing a quantum dot photoresist film, comprising: S1: injecting tri-n-octylphosphine into a first precursor at 320°C to 350°C, and then injecting a selenium tributylphosphine precursor, reacting for 5 seconds to 60 seconds in a preset argon environment, and rapidly cooling to room temperature, and obtaining a CdSe-TOP core mother solution after purification; S2: mixing the CdSe-TOP core mother solution and a sulfur precursor, and injecting them into the first precursor at 290°C to 350°C, and obtaining a CdSe / CdS quantum dot solution after reaction; S3: mixing the CdSe / CdS quantum dot solution and a preset photoresist according to a preset first ratio to obtain a first composite; S4: spin coating the first composite onto a preset substrate at a preset first speed and a preset first time, and then soft-baking at a preset first temperature and a preset second time, exposing according to a preset exposure energy, and developing at a preset third time to obtain a first quantum dot photoresist film.
[0005] Optionally, the first precursor is prepared by mixing tri-n-octylphosphine oxide, a long-chain alkylphosphonic acid and a cadmium source; the selenium tributylphosphine precursor is prepared by mixing a selenium source and tributylphosphine; and the sulfur precursor is prepared by mixing a sulfur source and tri-n-octylphosphine in a preset argon environment and heating the mixture to 80°C to 110°C.
[0006] Optionally, in the first precursor, the molar ratio of long-chain alkylphosphonic acid to cadmium oxide ranges from 0.7 to 10; in the selenium tributylphosphine precursor, the molar concentration of selenium source and tributylphosphine is 0.01 mol / L to 1 mol / L; in the sulfur precursor, the molar concentration of sulfur is 0.2 mol / L to 2.5 mol / L.
[0007] Optionally, in step S1, the molar ratio of selenium in the selenium tributyl phosphine precursor to the tri-n-octyl phosphine is 0.01 to 1; the molar ratio of cadmium oxide in the first precursor to selenium in the selenium tributyl phosphine precursor is 0.1 to 10; in step S2, the molar ratio of sulfur in the sulfur precursor to CdSe in the CdSe-TOP core mother liquor is 1000 to 100000; the molar ratio of cadmium oxide in the first precursor to CdSe in the CdSe-TOP core mother liquor is 500 to 20000.
[0008] Optionally, the cadmium source is one or two or more of cadmium oxide, cadmium acetate, cadmium stearate, cadmium acetylacetonate, and dimethyl cadmium; the sulfur source is sulfur powder, thiourea, dodecanethiol, or octanethiol; and the selenium source is selenium powder or selenourea.
[0009] Optionally, in step S1, the cooling time to room temperature is 1 minute to 5 minutes; in step S2, the rapid injection is completed within 1 second to 2 seconds, and the reaction time after injecting the CdSe-TOP core mother solution and the sulfur precursor is 1 minute to 5 minutes.
[0010] Optionally, in step S4, the preset first rotation speed is 500 rpm, the preset first time is 10 seconds, the preset first temperature is 100°C, the preset second time is 6 minutes, the preset exposure energy is 100 mJ, and the preset third time is 90 seconds.
[0011] Optionally, in step S4, after the step of soft baking at the preset first temperature and the preset second time, a second soft baking is performed at the preset second temperature and the preset fourth time; the preset first rotation speed is 1000 rpm, the preset first time is 10 seconds, the preset first temperature is 90°C, the preset second time is 4 minutes, the preset exposure energy is 100 mJ, the preset third time is 60 seconds, the preset second temperature is 100°C, and the preset fourth time is 1.5 minutes.
[0012] Optionally, the preset first ratio of the CdSe / CdS quantum dot solution and the preset photoresist is 1:2.
[0013] In order to solve the above technical problems, another technical solution adopted in the embodiment of the present application is: to provide a quantum dot photoresist film, wherein the quantum dot photoresist film is prepared by the preparation method of the quantum dot photoresist film as described above.
[0014] Different from the related art, the quantum dot photoresist film preparation method and quantum dot photoresist film provided in the embodiments of the present application increase the activity of the precursor by adding a selenium-tributylphosphine precursor under high-temperature reaction, obtain a high-concentration cadmium selenide core, and synthesize green-luminescent CdSe / CdS quantum dots. When using the same weight of quantum dots, the mass absorption coefficient at 450 nanometers is effectively increased, while the mass absorption coefficient at 360 nanometers is not increased, and the exposure of the photoresist is not affected, thereby improving the quantum dot light conversion efficiency in the prepared quantum dot photoresist composite film, and avoiding the escape of blue light from the Micro-LED chip when realizing the Micro-LED full-color solution. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] One or more embodiments are exemplarily described by corresponding drawings, which do not constitute limitations on the embodiments. Elements with the same reference numerals in the drawings represent similar elements, and the figures in the drawings do not constitute proportional limitations unless otherwise stated.
[0016] Figure 1 It is a schematic diagram of the process of preparing the quantum dot photoresist film provided in the embodiment of the present application.
[0017] Figure 2 This is a UV-visible absorption spectrum of the traditional green luminescent CdSe / ZnS core-shell quantum dots provided in the examples of the present application.
[0018] Figure 3 This is a UV-visible absorption spectrum of the traditional green luminescent CdZnSeS / ZnS alloy quantum dots provided in the examples of the present application.
[0019] Figure 4 This is a UV-visible absorption spectrum of the green-luminescent CdSe / CdS quantum dots provided in the examples of the present application.
[0020] Figure 5 It is a schematic diagram of a columnar comparison of mass absorption coefficients of different green light-emitting quantum dots at 450 nanometers provided in an embodiment of the present application.
[0021] Figure 6It is a schematic diagram of the absorbance changes of green luminescent CdSe / CdS quantum dots, CdSe / ZnS core-shell quantum dots and CdZnSeS / ZnS alloy quantum dots provided in the embodiments of the present application.
[0022] Figure 7 It is a comparison diagram of the pure photoresist photo provided in the embodiment of the present application and the first quantum dot photoresist film photo prepared using a green CdSe / CdS quantum dot solution.
[0023] Figure 8 This is a microstructure diagram of a first quantum dot photoresist film of different thicknesses prepared using a green CdSe / CdS quantum dot solution provided in an embodiment of the present application.
[0024] Fig. 9 It is the UV-visible absorption spectrum of the red luminescent CdSe / ZnS core-shell quantum dots prepared in the comparative example of the present application.
[0025] Fig.10 It is the ultraviolet-visible absorption spectrum of the red luminescent CdSe / CdS quantum dots prepared in the comparative example of the present application.
[0026] Fig.11 It is the ultraviolet-visible absorption spectrum of the red luminescent CdZnSeS / ZnS alloy quantum dots prepared in the comparative example of the present application.
[0027] Fig.12 Schematic diagram of the comparison of the mass absorption coefficients of red-light-emitting CdSe / CdS quantum dots, CdZnSeS / ZnS alloy quantum dots and CdSe / ZnS core-shell quantum dots at 450 nanometers provided in the embodiments of the present application.
[0028] Fig.13 It is a schematic diagram of the absorbance changes of red CdSe / CdS quantum dots, CdZnSeS / ZnS alloy quantum dots and CdSe / ZnS core-shell quantum dots prepared in the comparative example of the present application.
[0029] Fig.14 This is a microstructure diagram of a second quantum dot photoresist film of different thicknesses prepared using a red CdSe / CdS quantum dot solution provided in the comparative example of the present application.
[0030] Fig.15 It is a microstructure diagram of a third quantum dot photoresist film of different thicknesses prepared using a green CdZnSeS / ZnS alloy quantum dot solution provided in the comparative example of the present application.
[0031] Fig.16 This is a microstructure diagram of a fourth quantum dot photoresist film of different thicknesses prepared using a red CdZnSeS / ZnS alloy quantum dot solution provided in the comparative example of the present application. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of the present application more clearly understood, the following embodiments are provided in order to better further understand the present invention, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the present invention with the features of other prior arts shall fall within the protection scope of the present invention.
[0033] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0034] Unless otherwise defined, all technical and scientific terms used in this specification have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this specification includes any and all combinations of one or more of the related listed items.
[0035] The following specific examples are further explanations of the present invention. The examples cited cannot list all the embodiments of the present invention. Only some of the embodiments are used as examples for explanation. The specific examples are as follows:
[0036] The selenium tributylphosphine (Se-TBP) precursor and the sulfur precursor used in each example and comparative example were prepared in advance.
[0037] As an example, the configuration of the selenium tributylphosphine precursor used in each embodiment and comparative example is:
[0038] 4 mmol of selenium powder (selenium source) was weighed, and then 4 ml (16.2 mmol) of tributylphosphine (TBP) was added to obtain the selenium tributylphosphine precursor with a selenium concentration of 1 mol / L.
[0039] As an example, the sulfur precursor used in each embodiment and comparative example is prepared as follows:
[0040] 7.5 mmol sulfur (sulfur source) was dissolved in 3 ml (6.7 mmol) of tri-n-octylphosphine (TOP), and the mixture was mixed and heated to 80° C. to 110° C. in a preset argon environment to prepare the sulfur precursor with a sulfur concentration of 2.5 mol / L.
[0041] As another example, the sulfur source is sulfur powder, thiourea, dodecanethiol or octanethiol; the selenium source is selenium powder or selenourea.
[0042] Example 1
[0043] This embodiment 1 provides a method for preparing a quantum dot photoresist film. Figure 1 , Figure 1 : is a schematic diagram of a process for preparing a quantum dot photoresist film provided in an embodiment of the present application, and the specific steps are as follows:
[0044] S1: Inject tri-n-octylphosphine into the first precursor at 320°C to 350°C, and then inject selenium tributylphosphine precursor, react for 5 seconds to 60 seconds under a preset argon environment, and quickly cool to room temperature to obtain a CdSe-TOP core mother liquor (i.e., a synthetic CdSe-TOP core mother liquor) after purification.
[0045] Specifically, first prepare the first precursor, weigh 3.9mmol tri-n-octylphosphine oxide (TOPO), 0.18mmol octadecylphosphonic acid (ODPA) (i.e., long-chain alkylphosphonic acid) and 0.23mmol cadmium oxide (CdO) (i.e., cadmium source) and mix them in a 50mL flask, heat to 150°C, and expose them alternately in vacuum and argon for more than 5 times until the cadmium oxide appears as a brown solid and the rest appears as a colorless liquid, and then heat the solution to 320°C under an argon atmosphere, dissolve the cadmium oxide, and obtain the first precursor.
[0046] As some optional embodiments, in the first precursor, the molar ratio of long-chain alkyl phosphonic acid (such as the above-mentioned octadecyl phosphonic acid) to cadmium oxide ranges from 0.7 to 10; in the selenium tributyl phosphine precursor, the molar concentration range of selenium source and tributyl phosphine is 0.01 mol / L to 1 mol / L; in the sulfur precursor, the molar concentration of sulfur is 0.2 mol / L to 2.5 mol / L.
[0047] As other optional implementations, the cadmium source is one or two or more of cadmium oxide, cadmium acetate, cadmium stearate, cadmium acetylacetonate, and dimethyl cadmium.
[0048] Then, the CdSe-TOP core mother solution is synthesized again, 3.4 mmol of tri-n-octylphosphine (TOP) is injected into the first precursor at 320°C, and then a selenium tributylphosphine precursor is injected, the reaction is kept in a boiling state for 5 to 50 seconds under a preset argon environment, the heat source is removed, the mixture is cooled naturally, and the mixture is cooled to room temperature. An equal volume of n-hexane and twice the volume of anhydrous ethanol are added, and a solid is obtained after centrifugation. The solid is dissolved with n-hexane, ethanol is added, and the mixture is centrifuged to obtain a CdSe quantum dot precipitate. The CdSe quantum dot precipitate is dispersed in a tri-n-octylphosphine solution to obtain the CdSe-TOP core mother solution, wherein the core particle size of the CdSe quantum dots is 2.2 nm and the core concentration is 7 mmol / L.
[0049] As some optional embodiments, the molar ratio of selenium in the selenium tributyl phosphine precursor to the tri-n-octyl phosphine is 0.01 to 1; the molar ratio of cadmium oxide in the first precursor to selenium in the selenium tributyl phosphine precursor is 0.1 to 10
[0050] As some other optional embodiments, the time for cooling to room temperature during the synthesis of the CdSe-TOP core mother solution is 1 minute to 5 minutes.
[0051] S2: Mix the CdSe-TOP core mother solution and the sulfur precursor, and inject them into the first precursor at 290°C to 350°C, and obtain a CdSe / CdS quantum dot solution after the reaction (i.e., prepare a CdSe / CdS quantum dot solution), and the CdSe / CdS quantum dot solution emits green light.
[0052] Specifically, 1.5 ml of the CdSe-TOP core mother solution was mixed with 3 mL of the sulfur body, ultrasonically vibrated for 5 minutes, and rapidly injected into the first precursor prepared in this step at 350° C. and reacted for 4 minutes to obtain the green CdSe / CdS quantum dot solution.
[0053] Furthermore, the mass absorption coefficient of the green CdSe / CdS quantum dot solution obtained in step S2 is also detected. Figures 2 to 5 , Figure 2 is the UV-visible absorption spectrum of the traditional green luminescent CdSe / ZnS core-shell quantum dots provided in the embodiment of the present application, such as Figure 2 As shown, the concentration of green CdSe / ZnS core-shell alloy quantum dots is 0.41 mg / ml, and the absorbance of green CdSe / ZnS core-shell alloy quantum dots at a wavelength of 450 nm is 0.1621 at this concentration. Figure 3 is the UV-visible absorption spectrum of the traditional green luminescent CdZnSeS / ZnS alloy quantum dots provided in the embodiment of the present application, such as Figure 3 As shown, the concentration of green CdZnSeS / ZnS alloy quantum dots is 0.422 mg / ml, and the absorbance of green CdZnSeS / ZnS alloy quantum dots at a wavelength of 450 nm is 0.1469 at this concentration. Figure 4 is the UV-visible absorption spectrum of the green luminescent CdSe / CdS quantum dots provided in the embodiment of the present application, such as Figure 4 As shown, the concentration of green CdSe / CdS quantum dots is 0.122 mg / ml, and the absorbance of green CdSe / CdS quantum dots at a wavelength of 450 nm is 0.774 at this concentration. Figure 54 is a comparative diagram of the mass absorption coefficients of different green light-emitting quantum dots at 450 nanometers provided in the embodiment of the present application. In addition, the mass absorption coefficient can also be calculated according to the Lambert-Beer law. The result is as follows: Figure 5 As shown, the mass absorption coefficient of green CdSe / ZnS core-shell alloy quantum dots at 450nm is 0.3479L / (g·cm), the mass absorption coefficient of green CdZnSeS / ZnS alloy quantum dots at 450nm is 0.3973L / (g·cm), and the mass absorption coefficient of green CdSe / CdS quantum dots at 450nm is 6.35L / (g·cm). According to the comparison of the aforementioned mass absorption coefficients, the mass absorption coefficient of the green luminescent CdSe / CdS quantum dots obtained in the embodiment of the present application at 450 nanometers can be effectively increased by more than 16 times. Therefore, by utilizing the structure of the CdS shell layer, the absorption effect of green luminescent quantum dots on blue light can be effectively improved, so that the construction of green luminescent quantum dot photoresist color conversion film can be realized with fewer quantum dots.
[0054] As some optional embodiments, the molar ratio of sulfur in the sulfur precursor to CdSe in the CdSe-TOP core mother solution is 1000 to 100000; the molar ratio of cadmium oxide in the first precursor to CdSe in the CdSe-TOP core mother solution is 500 to 20000.
[0055] As some other optional implementations, the time for rapidly injecting the first precursor is 1 to 2 seconds, and the reaction time after injecting the CdSe-TOP core mother solution and the sulfur precursor is 1 to 5 minutes.
[0056] In addition, when mixing quantum dots with photoresist and performing the photolithography step, the absorbance of quantum dots at 365 nm still needs to be considered during the photolithography process. Figure 6 , Figure 6The present invention provides a schematic diagram of the absorbance change of green luminescent CdSe / CdS quantum dots, CdSe / ZnS core-shell quantum dots and CdZnSeS / ZnS alloy quantum dots. According to the aforementioned comparison diagram, the ratio of the absorption mass coefficient of the green luminescent CdSe / CdS quantum dots prepared in the present invention embodiment at 450 nanometers to the absorption mass coefficient at 365 nanometers is 0.588 (the value of the absorbance at 365nm is 1), while the ratio of the green luminescent CdZnSeS / ZnS alloy quantum dots is 0.1456, and the ratio of the CdSe / ZnS core-shell quantum dots is 0.2732. The green luminescent CdSe / CdS quantum dots prepared in the present invention embodiment, under the same blue light conversion efficiency, the absorption of 365nm is only 25% of that of the traditional alloy quantum dots, that is, the absorption of the quantum dots to the exposure light source can be effectively reduced, and the exposure effect of the quantum dots-photoresist can be improved.
[0057] Then, a quantum dot photoresist film is prepared according to the obtained CdSe / CdS quantum dot solution.
[0058] S3: mixing the CdSe / CdS quantum dot solution and a preset photoresist according to a preset first ratio to obtain a first composite.
[0059] S4: spin coating the first composite onto a preset substrate at a preset first rotation speed and a preset first time, then soft-baking at a preset first temperature and a preset second time, exposing according to a preset exposure energy, and developing at a preset third time to obtain a first quantum dot photoresist film.
[0060] As some optional embodiments, the preset first rotation speed is 500 rpm, the preset first time is 10 seconds, the preset first temperature is 100°C, the preset second time is 6 minutes, the preset exposure energy is 100 mJ, and the preset third time is 90 seconds.
[0061] As other optional embodiments, after the step of soft baking at a preset first temperature and a preset second time, a second soft baking is performed at a preset second temperature and a preset fourth time; the preset first rotation speed is 1000 rpm, the preset first time is 10 seconds, the preset first temperature is 90°C, the preset second time is 4 minutes, the preset exposure energy is 100 mJ, the preset third time is 60 seconds, the preset second temperature is 100°C, and the preset fourth time is 1.5 minutes.
[0062] As some further optional implementation manners, the preset first ratio of the CdSe / CdS quantum dot solution and the preset photoresist is 1:2.
[0063] See also Figure 7 , Figure 7 This is a comparison diagram of a pure photoresist photograph provided in an embodiment of the present application and a first quantum dot photoresist film photograph prepared using a green CdSe / CdS quantum dot solution. As shown in the figure, the first quantum dot photoresist film is significantly green.
[0064] See also Figure 8 , Figure 8 is a microstructure diagram of a first quantum dot photoresist film of different thicknesses prepared using a green CdSe / CdS quantum dot solution provided in an embodiment of the present application, Fig. 9 The upper part is 10 microns thick. Fig. 9 The lower part is 50 microns thick.
[0065] Comparative Example 1
[0066] This comparative example 1 provides a method for preparing a quantum dot photoresist film, which differs from Example 1 in that, in the step of synthesizing the CdSe-TOP core mother solution in comparative example 1, the tributylphosphine in the selenium tributylphosphine precursor is replaced with tri-n-octylphosphine, and the other conditions remain unchanged (the obtained CdSe / CdS quantum dot solution emits red light).
[0067] Please continue reading Figures 9 to 12 , Fig. 9 is the UV-visible absorption spectrum of the red luminescent CdSe / ZnS core-shell quantum dots prepared in the comparative example of the present application, such as Fig. 9 As shown, the concentration of the red-luminescent CdSe / ZnS core-shell quantum dots is 0.138 mg / ml, and the absorbance of the red-luminescent CdSe / ZnS core-shell quantum dots at 450 nm is 0.4057 at this concentration. Fig.10 is the UV-visible absorption spectrum of the red luminescent CdSe / CdS quantum dots prepared in the comparative example of the present application, such as Fig.10 As shown, the concentration of red CdSe / CdS quantum dots is 0.168 mg / ml, and the absorbance of red CdSe / CdS quantum dots at 450 nm is 0.742 at this concentration. Fig.11 is the UV-visible absorption spectrum of the red luminescent CdZnSeS / ZnS alloy quantum dots prepared in the comparative example of the present application, such as Fig.11 As shown, the concentration of the red CdZnSeS / ZnS alloy quantum dots is 0.158 mg / ml, and the absorbance of the red CdZnSeS / ZnS alloy quantum dots at 450 nm is 0.443 at this concentration. Fig.12: is a columnar comparison diagram of the mass absorption coefficients of red luminescent CdSe / CdS quantum dots, CdZnSeS / ZnS alloy quantum dots and CdSe / ZnS core-shell quantum dots at 450 nanometers provided in the embodiments of the present application. The mass absorption coefficients can be calculated according to the Lambert-Beer law. The results are as follows: Fig.12 As shown, the mass absorption coefficient of red CdZnSeS / ZnS alloy quantum dots at 450 nanometers is 2.81L / (g·cm), the mass absorption coefficient of red CdSe / CdS quantum dots at 450 nanometers is 4.41L / (g·cm), and the mass absorption coefficient of red CdSe / ZnS core-shell quantum dots at 450 nanometers is 2.94L / (g·cm). According to the comparison of the mass absorption coefficient of the aforementioned alloy quantum dots and the mass absorption coefficient of the red luminescent CdSe / CdS quantum dots, it is found that the mass absorption coefficient of the red luminescent quantum dots is increased by 1.57 times.
[0068] Please continue reading Fig.13 , Fig.13 Schematic diagram of the absorbance change of red luminescent CdSe / CdS quantum dots, CdZnSeS / ZnS alloy quantum dots and CdSe / ZnS core-shell quantum dots prepared in the comparative example of the present application. Fig.13 As shown, the ratio of the absorption mass coefficient of the red CdSe / CdS quantum dots at 450 nanometers to the absorption mass coefficient at 365 nanometers is 0.5653 (the absorbance value at 365 nm is 1), while the ratio of the red CdZnSeS / ZnS alloy quantum dots is 0.4748, and the ratio of the red CdSe / ZnS core-shell quantum dots is 0.5153, that is, the red CdSe / CdS quantum dots have no significant difference from the traditional alloy quantum dots during the photoresist exposure process.
[0069] A second quantum dot photoresist film can be obtained by using a red CdSe / CdS quantum dot solution and a preset first photoresist according to the aforementioned quantum dot photoresist film preparation steps.
[0070] See also Fig.14 , Fig.14 This is a microstructure diagram of a second quantum dot photoresist film of different thicknesses prepared using a red CdSe / CdS quantum dot solution provided in the comparative example of the present application. Fig.14 The upper part is 10 microns thick. Fig.14 The lower part is 50 microns thick.
[0071] Comparative Example 2
[0072] This comparative example 2 provides a method for preparing a quantum dot photoresist film, which differs from Example 1 in that in comparative example 2, a traditional green CdZnSeS / ZnS alloy quantum dot solution is used to replace the green CdSe / CdS quantum dot solution, and other conditions remain unchanged.
[0073] A third quantum dot photoresist film can be obtained by using a conventional green CdZnSeS / ZnS alloy quantum dot solution and a preset first photoresist according to the aforementioned quantum dot photoresist film preparation steps.
[0074] See also Fig.15 , Fig.15 This is a microstructure diagram of a third quantum dot photoresist film of different thicknesses prepared using a green CdZnSeS / ZnS alloy quantum dot solution provided in the comparative example of the present application. Fig.15 The upper part is 10 microns thick. Fig.15 The lower part is 50 microns thick, as shown in the figure. In order to improve the blue light conversion efficiency, the quantum dot concentration needs to be increased, and the dispersion of quantum dots in photoresist is limited. Therefore, in the high-concentration green light-emitting quantum dot system, the structural quality of the third quantum dot photoresist film is poor and does not meet the full-color solution of Micro-LED.
[0075] Comparative Example 3
[0076] This comparative example 3 provides a method for preparing a quantum dot photoresist film, which differs from Example 1 in that in comparative example 3, a traditional red CdZnSeS / ZnS alloy quantum dot solution is used to replace the green CdSe / CdS quantum dot solution, and other conditions remain unchanged.
[0077] A fourth quantum dot photoresist film can be obtained by using a conventional red CdZnSeS / ZnS alloy quantum dot solution and a preset first photoresist according to the aforementioned quantum dot photoresist film preparation steps.
[0078] See also Fig.16 , Fig.16 This is a microstructure diagram of a fourth quantum dot photoresist film of different thicknesses prepared using a red CdZnSeS / ZnS alloy quantum dot solution provided in the comparative example of the present application. Fig.16 The upper part is 10 microns thick. Fig.16 The lower part is 50 microns thick.
[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Under the concept of the present application, the technical features in the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other changes in different aspects of the present application as described above, which are not provided in detail for the sake of simplicity. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some of the technical features can be replaced by equivalents. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a quantum dot photoresist film, characterized in that: include: S1: injecting tri-n-octylphosphine into the first precursor at 320° C. to 350° C., and then injecting selenium tributylphosphine precursor, reacting for 5 seconds to 60 seconds under a preset argon environment, and rapidly cooling to room temperature to obtain a CdSe-TOP core mother solution after purification; S2: mixing the CdSe-TOP core mother solution and the sulfur precursor, and injecting them into the first precursor at 290° C. to 350° C. to obtain a CdSe / CdS quantum dot solution after reaction; S3: mixing the CdSe / CdS quantum dot solution and a preset photoresist according to a preset first ratio to obtain a first composite; S4: spin coating the first composite onto a preset substrate at a preset first rotation speed and a preset first time, then soft-baking at a preset first temperature and a preset second time, exposing according to a preset exposure energy, and developing at a preset third time to obtain a first quantum dot photoresist film.
2. The method for preparing a quantum dot photoresist film according to claim 1, characterized in that: The first precursor is prepared by mixing tri-n-octylphosphine oxide, long-chain alkylphosphonic acid and a cadmium source; The selenium tributylphosphine precursor is prepared by mixing a selenium source and tributylphosphine; The sulfur precursor is prepared by mixing a sulfur source and tri-n-octylphosphine in a preset argon environment and heating the mixture to 80° C. to 110° C.
3. The method for preparing a quantum dot photoresist film according to claim 2, characterized in that: In the first precursor, the molar ratio of the long-chain alkylphosphonic acid to cadmium oxide ranges from 0.7 to 10; In the selenium tributylphosphine precursor, the molar concentration range of the selenium source and tributylphosphine is 0.01 mol / L to 1 mol / L; In the sulfur precursor, the molar concentration of sulfur is 0.2 mol / L to 2.5 mol / L.
4. The method for preparing a quantum dot photoresist film according to claim 3, characterized in that: In step S1, the molar ratio of selenium in the selenium tributylphosphine precursor to the tri-n-octylphosphine is 0.01 to 1; the molar ratio of cadmium oxide in the first precursor to selenium in the selenium tributylphosphine precursor is 0.1 to 10; In step S2, the molar ratio of sulfur in the sulfur precursor to CdSe in the CdSe-TOP core mother solution is 1000 to 100000; the molar ratio of cadmium oxide in the first precursor to CdSe in the CdSe-TOP core mother solution is 500 to 20000.
5. The method for preparing a quantum dot photoresist film according to claim 2, characterized in that: The cadmium source is one or two or more of cadmium oxide, cadmium acetate, cadmium stearate, cadmium acetylacetonate, and dimethyl cadmium; The sulfur source is sulfur powder, thiourea, dodecanethiol or octanethiol; The selenium source is selenium powder or selenourea.
6. The method for preparing a quantum dot photoresist film according to claim 1, characterized in that: In step S1, the cooling time to room temperature is 1 minute to 5 minutes; In step S2, the rapid injection is completed within 1 to 2 seconds, and the reaction time after the injection of the CdSe-TOP core mother solution and the sulfur precursor is 1 to 5 minutes.
7. The method for preparing a quantum dot photoresist film according to claim 1, characterized in that: In step S4, the preset first rotation speed is 500 rpm, the preset first time is 10 seconds, the preset first temperature is 100°C, the preset second time is 6 minutes, the preset exposure energy is 100 mJ, and the preset third time is 90 seconds.
8. The method for preparing a quantum dot photoresist film according to claim 1, characterized in that: In step S4, after the step of soft baking at the preset first temperature and the preset second time, soft baking is performed again at the preset second temperature and the preset fourth time; The preset first rotation speed is 1000 rpm, the preset first time is 10 seconds, the preset first temperature is 90°C, the preset second time is 4 minutes, the preset exposure energy is 100 mJ, the preset third time is 60 seconds, the preset second temperature is 100°C, and the preset fourth time is 1.5 minutes.
9. The method for preparing a quantum dot photoresist film according to claim 1, characterized in that: The preset first ratio of the CdSe / CdS quantum dot solution and the preset photoresist is 1:
2.
10. A quantum dot photoresist film, characterized in that: The quantum dot photoresist film is prepared by the method for preparing a quantum dot photoresist film according to any one of claims 1 to 9.
